Religion beyond its private role in modern society - Hofstee, Wim; Kooij, Arie van der, 1945- (Leiden : BRILL, 2013)
The volume Religion beyond its Private Role in Modern Society aims at contributing to the debate on the distinction between public and private spheres with regard to the role of religion in modern societies.
Some Thoughts on Privatisation and De-institutionalisation: Religion in the Public SphereReligion in Liquid Modernity: Collective Manifestations of Religion in Secularizing Dutch Society; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Freedom of religion; Religion and sociology; Freedom of religion; Religion and sociology; BODY, MIND & SPIRIT -- Gaia & Earth Energies; RELIGION -- Christianity -- General; Freedom of religion; Religion and sociology; Electronic books; Electronic books